2018
DOI: 10.1503/cjs.009717
|View full text |Cite
|
Sign up to set email alerts
|

Management of intra-abdominal vascular injury in trauma laparotomy: a South African experience

Abstract: The mortality rate for IAVI remains high despite decades of operative experience in high-volume centres. Open operative techniques alone are unlikely to achieve further reduction in mortality rates. Integration of endovascular techniques may provide an alternative strategy to improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
7
0
4
Order By: Relevance
“…Previous studies have demonstrated a direct correlation between the number of concomitant injuries, and mortality rates in patients with PAAI. 2,4,18,19 For example, Tybursky et al found a mortality rate of 64% in patients with an ISS ≥25 compared to 23% in patients with an ISS <25 after abdominal vascular injury. 19 In addition, they found a 100% mortality rate in patients with injury to 4 or more intra-abdominal blood vessels after penetrating injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a direct correlation between the number of concomitant injuries, and mortality rates in patients with PAAI. 2,4,18,19 For example, Tybursky et al found a mortality rate of 64% in patients with an ISS ≥25 compared to 23% in patients with an ISS <25 after abdominal vascular injury. 19 In addition, they found a 100% mortality rate in patients with injury to 4 or more intra-abdominal blood vessels after penetrating injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In the grouped series analysis of selected civilian trauma, 4,890 injuries were identified in 3,599 patients 5 , 10 - 17 ). .…”
Section: Epidemiologymentioning
confidence: 99%
“…En el análisis agrupado de series seleccionadas de trauma civil se identificaron 4,890 lesiones en 3,599 pacientes 5 , 10 - 17 . Cuando se consideró el grupo de pacientes que requirieron tratamiento quirúrgico, las lesiones venosas sistémicas representaron el 48% de todas las lesiones, las del sistema porta el 11% y las arteriales el 41% ( Tabla 1 ).…”
Section: Epidemiologíaunclassified
“…O trauma vascular representa um grande desafio para os profissionais da saúde, pois apresenta altas taxas de morbidade e de mortalidade, a qual pode chegar a 39%, principalmente devido a exsanguinação, que também causa coagulopatias (TALBOT et al, 2019;PRICHAYUDH et al, 2018;WEALE et al, 2018). Além disso, os traumas vasculares são raros e habitualmente estão associados a outras lesões, como traumatismo craniano, lesão de órgãos sólidos e/ou ocos, as quais podem tornar o tratamento mais desafiador (KOBAYASHI et al, 2020;KOBAYASHI et al, 2016).…”
Section: Definiçãounclassified